Clutter Modeling for Ground-Penetrating Radar Measurements in Heterogeneous Soils - Takahashi, Kazunori; Igel, Jan; Preetz, Holger (IEEE journal of selected topics in applied earth observations and remote sensing, 2011)
Ground-penetrating radar (GPR) measurement and its interpretation/analysis are challenging when soil is heterogeneous. Soil heterogeneity causes unwanted reflections (i.e., clutter) that disturb reflections from objects of interest. Thorough investigations on soil heterogeneity and clutter are important in order to understand the influence on GPR and assess the performance. In order to observe the influence of heterogeneous soil, an irrigation test was carried out and GPR data were collected after the irrigation and while the distribution of soil water content varied. The correlation length and variability of the dielectric constant of soil were determined by geostatistical analyses of the GPR data. These two parameters were built into a simple model and the Mie solution was theoretically calculated. From this, the power of the backscattered field due to soil heterogeneity was modeled. The results were in agreement with the power of the clutter extracted from the GPR data. Therefore, clutter can be predicted from soil heterogeneity with a simple model using the Mie solution. Furthermore, the result exhibits that scattering by heterogeneous soil is dominated by Mie scattering, rather than Rayleigh scattering, in the studied frequency range.